Research Lumbar Punctures among African Americans and Caucasians: Perception Predicts Experience - Howell, Jennifer C.; Parker, Monica W.; Watts, Kelly D.; Kollhoff, Alexander; Tsvetkova, Dobromira Z.; Hu, William T. (Frontiers in Aging Neuroscience, 2016)
African Americans are under-represented in Alzheimer’s disease (AD)-related biomarker studies, and it has been speculated that mistrust plays a major factor in the recruitment of African Americans for studies involving invasive procedures such as the lumbar puncture (LP). We set out to determine factors associated with non-participation in a biomarker study aiming to explore cerebrospinal fluid AD biomarker differences between older African Americans and Caucasians. We also surveyed participants' procedure-related perception (a standard medical procedure vs. a frightening invasive procedure) and reluctance, as well as the rate and type of post-procedure discomfort and complications. Among 288 subjects approached for study participation, 145 (50.3%) refused participation with concerns over LP being the most commonly reported reason. Relatively more African Americans than Caucasians reported concerns over LP as the main reason for non-participation (46% vs. 25%, p=0.03), but more African Americans also did not provide a specific reason for non-participation. Among those who completed study participation (including the LP), African Americans and Caucasians were similar in pre-LP perceptions and reluctance, as well as post-LP rates of discomfort or complication. Perceiving LP as a frightening invasive procedure, not race, is associated with increased likelihood of post-LP discomfort or complication (RR 6.2, 95% confidence interval 1.1-37.0). Our results indicate that LP is a well perceived procedure in a cohort of African American and Caucasian research participants, and is associated with few serious complications. The pre-procedure perception that the LP is a frightening invasive procedure significantly increases the risk of self-reported discomfort of complications, and African Americans may be more likely to turn down study participation because of the LP. Future studies will need to address factors associated with negative LP perceptions to further assure participants and reduce complication rates.